Evaluation of Soybean [Glycine Max (L.) Merrill] Germplasm at Multi-Environments of Nepal and Their Stability Assessment using AMMI and GGE Biplot Analysis - Ghimire, Netra Hari; Dhakal, Krishna Hari; Pandey, Madhav Prasad; Joshi, Bal Krishna (Journal of Nepal Agricultural Research Council, 2024)
A total of 150 soybean germplasms received from various sources were evaluated in a field study at DoAR, Dasharathpur; Surkhet, GLRP, Rampur, Chitwan, and NARC, Khumaltar, Lalitpur during the consecutive years of 2019 and 2020. The study employed an alfa lattice design with three replications to assess diversity, agronomic performance, and the selection of stable, early maturing, and high yielding genotypes from the inner terai to mid hills of Nepal released variety Puja and Tarkari Bhatmas-1 served as standard check. Major quantitative traits like days to flowering, days to maturity, plant height, number of primary branches per plant, number of nodes per plant, number of pods per plants, grain yield, biomass, harvest index and seed weight were recorded. A pooled mean analysis of variance revealed that all recorded traits were found significant difference for genotypic, environmental and genotypic by environmental effect at (p